INFLUENCE OF Al AND Mn IMPURITIES ON STRUCTURAL PROCESSESTRANSFORMATIONS IN COPPER ALLOYS - Lobodyuk, V. A.; Mukashev, K. M. (Journal of Emerging Technologies and Computing, 2020)
In the work on specific examples involving real copper-basedalloys containing 14 weight.%Al and 3 weight.%Mn, describes the results of astudy of the process of restoring the shape of a material that was defomatedaccording to the three-point bending scheme. The studies were carried out bymeasuring changes in the temperature dependence of the electrical resistance anddeflection of the sample, as well as by obtaining microelectronograms using anelectron microscope. Since SME alloys operate under conditions of mandatorythermal cycling, the elucidation of the thermal stability of these materials is ofpractical interest. It is established that martensitic crystals that occur in hardenedsamples have a high density of packing defects and thin twins formed on the(121) γ´ plane. One of the important features of the martensitic mechanism is theobligatory formation of martensite with defects, which is a fine structure. Bycomparing the curves of the electrical resistivity and the deflection, it was foundthat the temperature range of the increase in the deflection upon coolingcoincides with the temperature range of the direct martensitic transformation. Inaddition to stacking faults, thin twins with a thickness of 0.01-0.04 microns arealso observed in martensite crystals. It was found in the analysis that twinningin martensite occurs along the 121 γ´ plane. It is shown that the streakiness arising during martensitic transformations is caused by stacking faults, which liein the 121 plane at a high density of stacking faults.